2012
DOI: 10.1190/geo2011-0167.1
|View full text |Cite
|
Sign up to set email alerts
|

Detecting a salt dome overhang with magnetotellurics: 3D inversion methodology and synthetic model studies

Abstract: Detecting a salt dome overhang is known to be problematic by seismic methods alone. We used magnetotellurics (MT) as a complementary method to seismics to investigate the detectability of a salt dome overhang. A comparison of MT responses for 3D synthetic salt models with and without overhang shows that MT is very sensitive to shallow salt structures and suggests that it should be possible to detect an overhang. To further investigate the resolution capability of MT for a salt dome overhang, we performed a 3D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Our inversion is based on the 3-D MT inversion code x3Di and details about the method are described in Avdeev & Avdeeva (2009) and Avdeeva et al (2012). It employs a limited-memory quasiNewton optimization method to minimize a Tikhonov-type regularized objective function ϕ.…”
Section: N V E R S I O N M E T H O Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Our inversion is based on the 3-D MT inversion code x3Di and details about the method are described in Avdeev & Avdeeva (2009) and Avdeeva et al (2012). It employs a limited-memory quasiNewton optimization method to minimize a Tikhonov-type regularized objective function ϕ.…”
Section: N V E R S I O N M E T H O Dmentioning
confidence: 99%
“…, where W is finite-difference approximation of the Gradient operator, which controls model smoothness (for more details, see Avdeeva et al 2012).…”
Section: N V E R S I O N M E T H O Dmentioning
confidence: 99%
“…As the forward solver is the driving engine of an inversion algorithm, the inversion codes are also based on FD, FE and IE methods. For the inversion task of both workshops only FD (Mackie et al 2001;Siripunvaraporn et al 2005;Hautot et al 2007Hautot et al , 2011Siripunvaraporn & Egbert 2009;Egbert & Kelbert 2012) and IE (Avdeev & Avdeeva 2009;Avdeeva et al 2012) codes were used. The 3-D magnetotelluric inverse problem is far from being solved, but these codes using different inversion schemes showed that one can recover the conductivity structure of simple, synthetic test models reasonably well, to greater or less degrees depending on resolution and sensitivity.…”
Section: Different Algorithms and Approachesmentioning
confidence: 99%
“…Mackie et al 2001;Hautot et al 2007Hautot et al , 2011Egbert & Kelbert 2012) and Quasi-Newton (QN) methods (e.g. Avdeev & Avdeeva 2009;Avdeeva et al 2012) avoid both the explicit computation and storage of a full sensitivity matrix. Only the gradient vector of the objective functional is needed.…”
Section: Different Algorithms and Approachesmentioning
confidence: 99%
“…below highly heterogeneous basalt layers or in the presence of complex salt structures. In such situations, resistivity models obtained via MT inversion can for example be used to improve velocity models for seismic processing or in workflows for joint interpretation (Hovertsen et al, 1998;Key et al, 2006;Avdeeva et al, 2012).…”
Section: Introductionmentioning
confidence: 99%